Answer:
sin
(
x/
2
) = -
√
3
/2
Take the inverse sine of both sides of the equation to extract x
from inside the sine.
x/
2
=
arcsin
(
−
√
3/
2
)
The exact value of arcsin
(
−
√
3
/2
) is −
π
/3
.
/x
2
=
−
π
/3
Multiply both sides of the equation by 2
.
2
⋅
x
/2
=
2
⋅
(
−
π
/3
)
Simplify both sides of the equation.
x
=
−
2
π
/3
The sine function is negative in the third and fourth quadrants. To find the second solution, subtract the solution from 2
π
, to find a reference angle. Next, add this reference angle to π to find the solution in the third quadrant.
x
/2
=
2
π
+
π/
3
+
π
Simplify the expression to find the second solution.
x
=
2
π
/3
4
π
Add 4
π to every negative angle to get positive angles.
x
=
10
π
/3
The period of the sin
(
x
/2
) function is 4
π so values will repeat every 4
π radians in both directions.
x
=2
π
/3
+
4
π
n
,
10
π/
3
+
4
π
n
, for any integer n
Exclude the solutions that do not make sin
(
x
/2
)
=
−
√
3/
2 true.
x
=
10
π
/3
+
4
π
n
, for any integer n
Multiplying fractions by whole numbers:
1. You have to convert the whole number into an improper fraction.
2. You then multiply the fractions straight across.
Ex: 2/3 × 6 =2/3 × 6/1 = 2×6/3×1= 12/3= 4
Hello!
Your answer would be 6
Than basically means switching the numbers
So basically if you were to multiply 6 x 6 (6 times less than)
You would get 36. Then subtract.
42 - 36 = 6, which is your answer.
I hope this helps!
Im one Brainliest away from next rank, so if possible please consider!
To substitute, solve for one variable and then plug it into the other equation you have. In this problem, y is already solved for on the top equation (y=x+2), so you just stuff it into the second equation.
y = x + 2
3y = 4x - 2
3(x + 2) = 4x - 2
3x + 6 = 4x - 2
-x = -8
x = 8
y = x + 2 = 8 + 2 = 10
solution:
x = 8
y = 10
hope this helps!! :)